Keterkaitan antara Perilaku Merokok, Preferensi Waktu dan Pilihan Terhadap Resiko (Studi Kasus di Kota Surabaya) - Sugiharti, Lilik; Sukartini, Ni Made; Handriana, Tanti (Jurnal Ekonomi Kuantitatif Terapan, 2016)
Empirical studies focus on the behavioral agents such as smoking addiction reported there is ambiguity in preference between smokers and non smokers, in terms of time and risk attitude. Study focuses on times preference between smokers and non smokers come to difference conclusion. Some studies reported that smokers tend to behave impulsive in time preference task.  On the other hand, other studies reported that non smokers behave impulsive. This study applies task and metodelogy of Pla and Jones (2003). Our study find there is no difference in time preference between smokers and non smokers, but compare to their counterpart, the smokers indeed avoid risky choices.
Keywords: Addiction behavior; smoking; time preferences